Serial changes in the side-branch ostial area after main-vessel stenting with kissing balloon inflation for coronary bifurcation lesions, assessed by 3D optical coherence tomography. (23rd October 2017) - Fujimura, Tatsuhiro; Okamura, Takayuki; Tateishi, Hiroki; Nakamura, Takeshi; Yamada, Jutaro; Oda, Tetsuro; Mochizuki, Mamoru; Nishimura, Shigehiko; Nishimura, Takashi; Yano, Masafumi
Abstract: Aims: We evaluated the influence of the jailing configuration and guidewire rewiring position in front of the side-branch (SB) ostium before kissing balloon inflation (KBI) against side-branch ostial area (SBOA) at follow-up using 3D optical coherence tomography (3D-OCT). Methods and results: We retrospectively analysed the cases of the 37 consecutive patients who underwent main-vessel (MV) stenting with KBI for coronary bifurcation lesion under OCT guidance and the follow-up OCT 6–12 months. We divided the patients into two groups, considering both the jailing configuration and the rewiring position by 3D-OCT. We defined the cases that achieved both the distal rewiring and link-free carina configuration as the FCD group, and the other cases were defined as the Non-FCD group. We compared the differences in the SBOA derived by the cut-plane analysis and the number of compartments between the two groups. The median and interquartile range of serial change and percent serial change in SBOA in the FCD group were significantly larger than those in the Non-FCD group [0.43 mm 2 (−0.29 to 0.91) vs. −0.65 mm 2 (−1.33 to 0.34); P = 0.0136 and 9.47% (−8.37 to 27.33) vs. −13.77% (−31.64 to 10.88); P = 0.0182]. Conclusion: This serial OCT study demonstrated that the achievement of both the distal rewiring and link-free carina configuration may be important for the preservation of the SBOA after MV stenting with KBI for coronary bifurcation lesions.